1983
DOI: 10.3168/jds.s0022-0302(83)81958-4
|View full text |Cite
|
Sign up to set email alerts
|

Propionate for Fatty Acid Synthesis by the Mammary Gland of the Lactating Goat

Abstract: Isolated mammary glands of lactating goats were perfused with heparinized and oxygenated blood for 8 to 15 h. Adequate quantities of glucose, acetate, and amino acid were added to the perfusate. After addition of propionate to the perfusion blood, concentrations of odd-numbered and of monomethyl-substituted fatty acids other than those with iso and anteiso configuration increased in the milk fat. These acids seem to be synthesized de novo in the mammary gland. The increase of C17:0 concentration was weak and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
4

Year Published

1994
1994
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 29 publications
4
37
0
4
Order By: Relevance
“…This decrease could be related to the negative effect on milk yield that seemed to be observed when glucose is infused with a corn based diet [24,27] or with diets rich in concentrates [29,43] [20] and Seal and Parker [38] with C3 infusion and as for Clark et al [6] and Amaral et al [1] [14], because C1! has a dual origin [25]. Results from Hurtaud et al [14] and Lemosquet et al [24] give similar support to the above possibilities.…”
Section: Statistical Analysessupporting
confidence: 75%
“…This decrease could be related to the negative effect on milk yield that seemed to be observed when glucose is infused with a corn based diet [24,27] or with diets rich in concentrates [29,43] [20] and Seal and Parker [38] with C3 infusion and as for Clark et al [6] and Amaral et al [1] [14], because C1! has a dual origin [25]. Results from Hurtaud et al [14] and Lemosquet et al [24] give similar support to the above possibilities.…”
Section: Statistical Analysessupporting
confidence: 75%
“…Comparison of the ratios of C15:0 to anteiso C15:0 fatty acids in jugular plasma (0.94) and milk fat (1.99) in the study of Loor et al (2005) also suggests a relative increase in C15:0 fatty acid in milk, although there was no corresponding increase for C17:0. Earlier studies have shown that the straight-chain fatty acids (C15:0 and C17:0) can be synthesized de novo from propionate (Scaife et al, 1978;Massart-Leën et al, 1983;Rigout et al, 2003). Rigout et al (2003) showed a relatively smaller response in C17:0 than C15:0 when infusing propionic acid into the rumen, perhaps reflecting a more limited ability to elongate C15:0 to C17:0, although desaturation of C17:0 to C17:1 might also have reduced the apparent effect (Fievez et al, 2003).…”
Section: Obcfamentioning
confidence: 97%
“…Odd-fatty acids in milk and dairy of cows could be reflecting rumen function (e.g., ruminal fermentation pattern, including methane, duodenal flow of microbial protein and acidosis) (Fievez et al, 2012). Endogenous chain elongation in the mammary gland using propionyl-CoA as a precursor (Dodds et al, 1981;Massart-Leen et al, 1983) explains the occurrence of C5:0, C7:0, C9:0 and C11:0 in milk and adds to odd-chain fatty acids transferred from the duodenum (C13:0, C15:0 and C17:0).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%